MUTUALISM IN LESSON STUDY - Patang Hafira (Institut Agama Islam Negeri Palopo, 2018)
Lesson study has commonly three stages in the implementation. They are plan, do, and see. In the process, a relationship occurs between people who are involved in it. They are the teachers, students, and observers. This research focuses about the positive relation happened between teachers and observers. Positive relation between people who are involved in learning process could improve classroom quality. The positive relation is named mutualism. In biological term, mutualism is when two organisms of different species